Computational Thinking Training and Its Implementation in Learning for MTS Teacher Noor Iman Samarinda - Rijal, Muhammad Khairul (TAFANI: Jurnal Pengabdian Masyarakat, 2022)
The 21st century is an era where changes occur rapidly. We need the right response in dealing with it. Computational Thinking (CT) is considered a suitable approach in the thinking process to solve problems quickly and precisely. CT is a development of the basic concepts of computer science. Indonesia, through the Bebras Community, has continued to campaign for CT for teachers and students since 2016. Sultan Aji Muhammad Idris State Islamic University (UINSI) as one of the Bebras Bureaus in East Kalimantan continues to strive to promote CT through many trainings for teachers and students in madrasas that is in East Kalimantan. One of the madrasas targeted for Computational Thinking (CT) training is MTS Noor Iman Samarinda. This training mechanism passes through five stages, namely determination, implementation, evaluation of implementation, control, and improvement (PPEPP). The training method is through presentation, practice, and discussion. The results of this training activity enable teachers to apply Computational Thinking (CT)-based questions and design learning in the classroom to be more fun and problem-solving oriented. Keywords: computational thinking, bebras, problem solving